TINGKAT AKSESIBILITAS KAWASAN TRANSIT STASIUN MANGGARAI, JAKARTA SELATAN - Galih Kusuma Adi; Aleksander Purba; Shahnaz Nabila Fuady (Jurnal Perencanaan dan Pengembangan Kebijakan, 2023)
Manggarai Station is one of DKI Jakarta Province's busiest stations. Manggarai Station's existence as a transit node promotes mobility from residential areas to the station. Many activities are impacted by land use around the station. In order to accommodate this matter, good accessibility is required. The development of the Manggarai Station area appears to follow the Transit Oriented Development concept (TOD). The implementation of the TOD concept is expected to improve the accessibility of the Manggarai Station transit area. As a result, the purpose of this research is to determine the level of accessibility of the Manggarai Station transit area.